2019
DOI: 10.1007/s12325-019-01191-2
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Serum IgE Concentration to Predict Exacerbation Risk and Benralizumab Efficacy for Patients with Severe Eosinophilic Asthma

Abstract: Introduction: For patients with eosinophilic asthma with allergic characteristics, understanding the key drivers of exacerbations is important to identify optimal treatment strategies. Benralizumab is an interleukin-5 receptor alpha-directed cytolytic monoclonal antibody that significantly reduces exacerbation frequency for patients with severe, uncontrolled eosinophilic asthma. We evaluated the predictive value of baseline blood eosinophil counts vs. serum immunoglobulin E (IgE) concentrations on exacerbation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 18 publications
3
43
0
2
Order By: Relevance
“…Hence, also these findings corroborate the results of recent pooled analyses of SIROCCO and CALIMA trials, which showed that the therapeutic effects of benralizumab were independent of IgE levels and atopic trait in subjects with severe eosinophilic asthma. 29 , 60 …”
Section: Discussionmentioning
confidence: 99%
“…Hence, also these findings corroborate the results of recent pooled analyses of SIROCCO and CALIMA trials, which showed that the therapeutic effects of benralizumab were independent of IgE levels and atopic trait in subjects with severe eosinophilic asthma. 29 , 60 …”
Section: Discussionmentioning
confidence: 99%
“…However, B-Eos have been shown to be significantly predictive of sputum eosinophilia [ 21 ]. In adults, numerous works observed the association between elevated B-Eos and asthma attacks, with increasing rate of hospitalization [ 24 , 42 , 43 ]. In childhood, the role of blood eosinophils in the prediction of asthma exacerbations has long been unclear.…”
Section: Biomarkersmentioning
confidence: 99%
“…In childhood, the role of blood eosinophils in the prediction of asthma exacerbations has long been unclear. Some studies stated the validity of this association in children and adolescents [ 18 , 19 , 22 , 24 ]; however, the cut-point of blood eosinophils for clinical detection of type 2 inflammation was not precisely determined. A retrospective study of children 5 to 11 years in a large medical care organization compared different B-Eos thresholds and identified an optimal cut-off of 300 cells/mL, which was associated with a 52% increase in asthma exacerbation rate [ 21 ].…”
Section: Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Jak pokazują metaanalizy, terapie antyeozynofilowe skierowane przeciwko IL-5 (mepolizumab, reslizumab) lub łańcuchowi α receptora dla IL-5 (benralizumab) redukują liczbę ciężkich zaostrzeń o połowę [44]. Efektywność terapii antyeozynofilowych potwierdzono zarówno w astmie atopowej, jak i nieatopowej, bez istotnej różnicy pomiędzy grupami [45,46].…”
Section: Eozynofile Jako Komórki Efektorowe W Zapaleniu Alergicznym Iunclassified